Histopathology of the salivary glands - Hellquist, Henrik (Springer Berlin Heidelberg, 2014)
Over the past 25 years it has become more and more evident that salivary gland pathology is by far the subject within head and neck pathology that causes the most diagnostic challenges and problems for general pathologists. Among the reasons for this are the relative rarity of salivary gland tumors (as a result of which the general pathologist does not gain sufficient personal experience in their diagnosis), their striking diversity (there are almost 40 different histological tumor entities), and the fact that some tumours dedifferentiate and some benign tumors progress to become malignant.   This book is a comprehensive guide to salivary gland pathology that illustrates almost every type of salivary gland tumor and will assist greatly in routine diagnostic work. Non-neoplastic lesions, benign epithelial tumors, malignant epithelial tumors, and non-epithelial and secondary tumors are all covered in detail, and the WHO and TNM classifications are clearly explained. Another significant feature is the incorporation of important knowledge gained during the past few years regarding the genetics of salivary gland tumors. Histopathology of the Salivary Glands will be of interest not only to pathologists but also to dentists, ENT and head and neck surgeons, and oncologists.